The Relation Between The Workload Of Nurse Executor And Work Stress In The Hospital Ward Of RSUD Sleman - Nur Yeti Syarifah (LPPM STIKES Guna Bangsa Yogyakarta, 2018)
Background: Job stress on nurses can be caused by various factors, one of which is the workload of nurses. Nurse is a benchmark that determines the quality of hospital health services, especially in inpatient wards.